ANESTESIA GERAL PARA CESARIANAS: ESTUDO RETROSPECTIVO DE INDICAÇÕES, TÉCNICAS E DESFECHOS RELACIONADOS EM UM HOSPITAL TERCIÁRIO - Corrêa, Eduardo Francisco Mafassioli (2019)
Cesarean delivery rate in Brazil is approximately 55%. Spinal anesthesia is preferred, because it's associated with less maternal complication rates, hasten the post anesthesia recovery and avoid fetal exposition to anesthetic drugs. General anesthesia (GA) is chosen when neuraxial anesthesia is contraindicated or when spinal anesthesia technique fails. Moreover, GA is chosen in emergent situations, when there's not sufficient time to perform neuraxial block. GA indications are been refined as new evidence support or refute this technique. There are plenty international scientific papers on GA in cesarean delivery, but none conducted in Brazil. Research articles rely on data and information accurately inserted in clinical records. However, oftenly, information is wrongly added to clinical records, compromising research results. General Objectives: Assess GA rate in cesarean deliveries that took place in high risk Pregnancy Center in southern Brazil. Specific Objectives: Identify main complications of GA in cesarean deliveries; Create a database software for research purposes, with complete and correct data; Methods: Retrospective analysis of medical record on deliveries with GA in a period of four consecutive years. After literature review, a form was elaborated with main information used on this research topic relevant to the current study. The collected data were analyzed using descriptive statistics. The database was developed by an information technology company based on the forms with medical records information. Results: During the researched period, 5,425 cesarean deliveries were performed, 109 under GA (2.0%). The most common indications where: Obstetric emergencies (45%), failure of neuraxial technique (32%) and contraindications to neuraxial anesthesia (23%). Pulmonary aspiration of gastric contents took place once and one maternal death after the delivery was observed, but not related to the anesthesia. Conclusions: 2% of GA in cesarean deliveries is low when compared with North American literature (5%). There is a global effort to reduce GA for cesarean deliveries, because, when compared with neuraxial anesthesia, it is associated with higher rates of anesthesia related 8 complications. The most frequent indication of GA was related to obstetric emergencies, in line with international literature. Product and applicability: The database software will be able to produce high quality results, as it will properly choose how and what data should be included, minimize data loss and can be updated periodically. This software can be shared with other facilities, collaborating to better understanding the obstetric practices in our country.